PENGEMBANGAN PARAGRAF DALAM NOVEL LASKAR PELANGI KARYA ANDREA HIRATA - Adesi, Putri (UNIB Press, 2022)
Novel is unique in their paragraph arrangement. The uniqueness of writing this paragraph is because novels are part of literary works in the form of prose fiction. Likewise, the novel Laskar Pelangi by Andrea Hirata is packaged with paragraphs that attract the reader's attention. For this reason, this research aims to describe the development of paragraphs in the novel Laskar Pelangi by Andrea Hirata. The data in this study are in the form of paragraphs, while the data source is the novel Laskar Pelangi by Andrea Hirata. The method used in this study is the method of content analysis, while the research design is Mayring's qualitative content analysis. Data collection techniques are documentation and note-taking techniques sourced from the novel Laskar Pelangi by Andrea Hirata. The main instrument in this research is the researcher and assisted by data tabulation. The data analysis technique begins with 1) formulating the problem to be researched, 2) creating categories, 3) searching for data with paragraph development categories according to its type, 4) formative examination, 5) summative checking, and 6) interpreting each paragraph development found. The results showed that the novel Laskar Pelangi by Andrea Hirata was developed using various paragraph developments, namely a) single-sentence paragraphs, b) descriptive paragraphs, c) informative paragraphs, d) dialogue paragraphs, and e) monologue paragraphs. The strength of the novel Laskar Pelangi by Andrea Hirata uses informative paragraph development because the development of informative paragraphs serves to inform the reader about the atmosphere, place and time of the event, so that the reader is carried away into the storyline.